2017
DOI: 10.1002/cam4.1067
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of cell cycle pathway genes predict disease‐free survival of hepatocellular carcinoma

Abstract: Disruption of the cell cycle pathway has previously been related to development of human cancers. However, associations between genetic variants of cell cycle pathway genes and prognosis of hepatocellular carcinoma (HCC) remain largely unknown. In this study, we evaluated the associations between 24 potential functional single nucleotide polymorphisms (SNPs) of 16 main cell cycle pathway genes and disease‐free survival (DFS) of 271 HCC patients who had undergone radical surgery resection. We identified two SNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…For example, Xie et al (2018) showed that DNA replication is associated with tumor cell proliferation and prognosis of patients with HCC. Moreover, genetic variations in cell cycle pathway genes affect the disease-free survival of patients with HCC ( Liu et al, 2017 ). The TP53 mutation is considered one of the molecular mechanisms of HCC pathogenesis ( Hussain et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Xie et al (2018) showed that DNA replication is associated with tumor cell proliferation and prognosis of patients with HCC. Moreover, genetic variations in cell cycle pathway genes affect the disease-free survival of patients with HCC ( Liu et al, 2017 ). The TP53 mutation is considered one of the molecular mechanisms of HCC pathogenesis ( Hussain et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, GO and KEGG analyses showed enrichment of both modules in multiple tumor-related pathways. For instance, DNA replication is associated with tumor cell proliferation and the prognosis of HCC ( Xie et al, 2018 ), variations in cell cycle pathway genes affect disease-free survival of patients with HCC ( Liu et al, 2017 ), TP53 mutation is considered one of the critical molecular mechanisms of HCC pathogenesis ( Hussain et al, 2007 ), an abnormal cellular senescence phenotype is observed in various cancer types ( Chen S. L. et al, 2019 ), and cytochrome P450 is severely damaged and dysregulated in HCC ( Yan et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well studied that cell cycle regulators are strongly implicated in progression of cancer development [ 16 ]. Disruption of the cell cycle pathway has previously been associated with development of several kinds of cancers, including HCC [ 17 ]. Although recent progress has enabled improved diagnosis and management of HCC, its prognosis remains dismal.…”
Section: Discussionmentioning
confidence: 99%
“…Reports indicate that changes in cell cycle rhythm are closely related to the occurrence and development of HCC. 31 The imbalance of the p53 signaling pathway promotes the proliferation of HCC cells, thereby contributing to the occurrence of HCC. 32 To further determine the key genes in the ceRNA network, we considered the top 10 genes in the PPI network as Hub genes including, CDK1, CCNA2, CCNB1, PPP2R1A, CHEK1, KIF23, BIRC5, OIP5, RAD51, and RACGAP1.…”
Section: Discussionmentioning
confidence: 99%